The Dynamics of 13–14-Year-Old Boxers' Memory Indicators - Nodirjon ugli, Gafforov Nosirjon (Journal of Innovation in Education and Social Research, 2024)
This study analyzes the dynamics of visual, mechanical, logical, short-term, and long-term memory indicators in 13-14-year-old boxers. The research compares the effects of different training methods on memory development in control (CG) and experimental (EG) groups. Statistical analysis was used to determine the differences between the groups and the development of each type of memory. The results show that both groups demonstrated gradual improvement in all memory types over four stages, but no significant statistical differences were found between the groups. These findings suggest that both training methods equally support cognitive development in young boxers.